A Systematic Approach Utilizing the System Engineering Initiative for Patient Safety 2.0 Model to Mitigate Fatigue in ER - Dian, Restuputri; Ananda, Zayra; Wardana, Rahmat; Masudin, Ilyas; Hidayati, Ika (Unnes Journal of Public Health, 2025)
The study focuses on addressing fatigue among healthcare workers in Emergency Room (ER), vital in delivering health services but prone to worker fatigue. Using objective measures like cardiovascular load (%CVL) and Bourdon Wiersma test, it evaluates physical and mental fatigue. Leveraging the System Engineering Initiative for Patient Safety 2.0 (SEIPS 2.0) model, it comprehensively analyzes factors affecting fatigue. Data collection includes surveys and statistical analysis through Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results show all workers experience fatigue, with physical fatigue affected by age and gender, and mental fatigue influenced by workload. The outer model analysis confirms convergent and discriminant validity, and reliability of the constructs. The inner model analysis reveals the work system significantly affects fatigue, while the process does not. The study emphasizes the importance of addressing fatigue to improve worker well-being and enhance patient care in ER, providing actionable insights for healthcare organizations.